Leisure preferences and perceptions of WMSU P.E. majors and non-majors - Labad, Elmer M.; Uy, Gilda L (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2003)
This study was conducted to analyze the activity preferences and leisure perceptions of PE Majors and Non-Majors in Western Mindanao State University, Zamboanga City. A questionnaire with a local reliability of 87%, was constructed for this purpose. An interview was employed to few respondents to obtain views, insights and reasons about their leisure participation. Stratified random sampling was used to identify the respondents in this study. Statistical Analyses were performed using the descriptive statistics (frequency, means, and percentages ), Analysis of variance (ANOVA), Cronbach's Alpha frequency of distribution, T-tests, Chi-Square, Pearson Correlation, and ETA Correlation. The computations were done using the Statistical Package for Social Science (SPSS) at .05% level of significance. Results of this study revealed that PE majors showed inclination to sports and vigorous leisure activities while Non-Majors manifested interests in spectator or passive type of leisure pursuits. Similar preferences and frequency of participation were reflected in activities like watching television, listening to music, talking to friends/neighboring and reading. Seven (7) factors were yielded in this study, which described their views on leisure participation. The perception factors that showed significant correlation with intervening variables are : interpersonal relationship (gender and ethnicity ); leisure venues personality (residence and grade eight average), and interpersonal effectiveness (residence and grade weight average). This study recommends the need to implement and intensify leisure programs in the school and emphasize the derivative values from participation. Future studies should involve large group of subjects and include other leisure activities that were not identified in this study.
"October 2003."
Thesis (M.S. Physical Education)--University of the Philippines Diliman
Keywords: Leisure -- Research -- Philippines -- Mindanao